Lopinavir/ Ritonavir, an Antiretroviral Drug, Lowers Sperm Quality and Induces Testicular Oxidative Damage in Rats (2015)
Lopinavir/Ritonavir (KaletraR) is a protease inhibitor used in the management of HIV infection. The increased incidence of toxicity of antiretroviral therapy (ART) has necessitated proper evaluation of their effects on reproductive health. Therefore, this study was designed to investigate the effects of KaletraR on male reproductive system in Wistar rat. Methods: Eighteen rats were assigned into three groups. The first group served as control while the second and third groups received KaletraR at therapeutic dose (8.3 mg/kg) (Kaletra-T) and twice therapeutic dose (16.6 mg/kg) (Kaletra-2T). KaletraR was given orally for 21 days. Administration of KaletraR caused a significant (p = 0.023) decrease in body weight-gain of rats. Precisely, Kaletra-T and Kaletra-2T decreased body weight-gain by 43% and 48%, respectively. Kaletra-T and kaletra-2T significantly (p = 0.016-0.036) decreased sperm motility and sperm count while kaletra-2T increased total sperm abnormalities in the rats. Also, KaletraR (at the two doses) caused a significant (p = 0.02-0.04) increase in the levels of testicular lipid peroxidation with a concomitant decrease in antioxidant indices. Specifically, Kaletra-T and Kaletra-2T decreased the activities of glutathione peroxidase by 38% and 57%, catalase by 40% and 48%, glutathione-s-transferase by 32% and 35% and superoxide dismutase by 47% and 52%, respectively while Kaletra-2T decreased reduced glutathione by 49%. Photomicrographs of testis from control and Kaletra-T groups showed normal seminiferous tubules with abundant spermatogenic cells while Kaletra-2T group had few and abnormal shape spermatogenic cells. KaletraR induces oxidative damage in testis of rats leading to changes in sperm characteristics and antioxidant status of the animals.